2016
DOI: 10.11138/ccmbm/2016.13.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of teriparatide vs alendronate in postmenopausal osteoporosis: a prospective non randomized clinical study

Abstract: SummaryIn this work we study the safety and effectiveness of teriparatide and alendronate in patients with postmenopausal osteoporosis at high risk of fracture; it was a double-blinded and it was done by examining the comparisons between teriparatide 20 μg /day and alendronate 10 mg/day. Safety and effectiveness analyses were based on data from 355 woman with a mean age of 68 years. Two groups (A and B) with T-score ≤-2.5 at bone mineral density were analyzed and 3 or more vertebral fractures on radiograph. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…These studies had shown that teriparatide is well tolerated and reduces the risk of vertebral and nonvertebral fractures. It is known to increase bone formation and treatment of osteoporosis with PTH causes a marked increase in vertebral BMD (BMD) and levels of bone turnover biomarkers in osteoporotic patients (9)(10)(11)(12)(13)(14). These data suggest a possible use of teriparatide in the treatment of this kind of disease and this study compares the classic accepted therapy using neridronate with off-label use of teriparatide.…”
Section: Introductionmentioning
confidence: 97%
“…These studies had shown that teriparatide is well tolerated and reduces the risk of vertebral and nonvertebral fractures. It is known to increase bone formation and treatment of osteoporosis with PTH causes a marked increase in vertebral BMD (BMD) and levels of bone turnover biomarkers in osteoporotic patients (9)(10)(11)(12)(13)(14). These data suggest a possible use of teriparatide in the treatment of this kind of disease and this study compares the classic accepted therapy using neridronate with off-label use of teriparatide.…”
Section: Introductionmentioning
confidence: 97%
“…Bisphosphonates are the cornerstone for the treatment of osteoporosis [5] and are commonly prescribed for its treatment, both in women and men [6]. More recently, other drugs (i.e., teriparatide and denosumab) are often prescribed and showed a safety profile [7], even when prescribed for therapy of non-unions [8]. However, a surgical approach sometimes necessary, in particular, in the case of vertebral compression fractures [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, systemic pharmacological therapy to improve bone metabolism may help improve the revascularization and osseointegration of allogenic bone grafts implanted during index revision surgery. Teriparatide (parathyroid hormone [PTH1-34]) is an anabolic agent reported to increase bone formation by stimulating osteoblast differentiation, function, and survival [ 21 , 22 ]. The application of teriparatide in fractures of animal models resulted in increased callus volume, as well as improved mineralization and mechanical strength [ 23 ].…”
Section: Discussionmentioning
confidence: 99%